Method for producing zinc oxide nanoparticles
Patent Information
- Application Number
- JP2021060690
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-03-31
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing zinc oxide nanoparticles. [Background technology]
[0002] Zinc oxide is used for a variety of purposes, including UV protection, sensors, conductive films, pharmaceuticals, catalysts, and rubber vulcanization accelerators (Non-Patent Documents 1 and 2). [Prior art documents] [Non-patent literature]
[0003] [Non-Patent Document 1] Resources and Materials, 113, No.6, 491 (1997) [Non-Patent Document 2] Zinc Oxide: Cutting-edge Technology and Future (CMC Publishing), 37 (2011) Summary of the Invention [Problem to be solved by the invention]
[0004] However, the above-mentioned conventional techniques have the following problems.
[0005] For applications such as ultraviolet shielding, sensors, conductive films, pharmaceuticals, catalysts, and rubber vulcanization accelerators, improved activity and transparency are required.
[0006] Conventionally, the industrial production methods for zinc oxide have involved heating and vaporizing metallic zinc and burning it with air, or pyrolyzing zinc sulfate or zinc nitrate, so there is a limit to how small the particle size of zinc oxide can be made.
[0007] For general pharmaceutical and rubber additive applications, the particle size of zinc oxide is 100 nm or more, and even what are called "ultrafine particles" have a particle size of 20 nm to 100 nm.
[0008] Conventionally, a method for synthesizing zinc oxide involves reacting a salt such as zinc chloride with a base such as sodium carbonate or sodium hydroxide. However, in the conventional method, the particle size is large, or at most 20 nm, and the zinc oxide is obtained as an aggregate. In the conventional method, the smaller the particle size of zinc oxide, the more difficult it is to filter and wash the zinc oxide, and it is difficult to remove the by-product salt.
[0009] Therefore, an object of the present invention is to easily obtain zinc oxide having high transparency.
[0010] Another object of the present invention is to obtain a highly safe and highly active antibacterial and antiviral material by using the zinc oxide. [Means for solving the problem]
[0011] In view of the above object, and as a result of extensive research, the present inventors have discovered that in a method for producing zinc oxide nanoparticles, zinc oxide having a size of 15 nm or less can be obtained by mixing zinc oxide and an organic acid in a specific ratio, thereby solving the above problem.
[0012] After further research, the present invention was completed.
[0013] That is, the present invention includes the following configurations.
[0014] Section 1. 1. A method for producing zinc oxide nanoparticles, comprising the steps of: Zinc oxide and an organic acid are mixed in a mass ratio of Mixing zinc oxide and organic acid in a ratio of 1:0.18 to 0.3; Manufacturing method.
[0015] The organic acid is mixed in a mass ratio of 0.18 to 0.3 for every 1 part of zinc oxide.
[0016] Section 2. The organic acid is acetic acid. The method for producing the same according to item 1.
[0017] Section 3. 1. Zinc oxide nanoparticles, The zinc oxide nanoparticles have an acyloxy group bonded to at least a part of the zinc oxide present on the surface, Specific surface area is 70m 2 / g or more, Zinc oxide nanoparticles.
[0018] The acyloxy group (RCOO-) is, for example, an acetoxy group (CH3COO-).
[0019] Section 4. When the zinc oxide nanoparticles are heated to 600°C using a thermogravimetric and differential thermal analyzer, the weight loss at 200°C or higher is 3% by mass or more. Item 4. The zinc oxide nanoparticles according to item 3.
[0020] Section 5. The zinc oxide nanoparticles have an average particle size of 15 nm or less. Item 3. The zinc oxide nanoparticles according to item 3 or 4.
[0021] Section 6. A photocatalyst comprising: The zinc oxide nanoparticles according to any one of items 3 to 5 are contained therein. Photocatalyst.
[0022] Section 7. A complex comprising: Item 6. The zinc oxide nanoparticles according to any one of items 3 to 5, and Titania nanoparticles, containing Complex.
[0023] Section 8. The titania nanoparticles have an average particle size of 30 nm or less. Item 8. The complex according to item 7.
[0024] Section 9. The titania nanoparticles have acetoxy groups bonded to at least some of the titanium atoms present on the surface, When the titania nanoparticles are heated to 600°C using a thermogravimetric and differential thermal analyzer, the weight loss at 200°C or higher is 5% by mass or more. Item 9. The complex according to item 7 or 8.
[0025] Section 10. A deodorizing material comprising: Contains zinc oxide nanoparticles and titania nanoparticles, The zinc oxide nanoparticles have an average particle size of 15 nm or less, The titania nanoparticles have an average particle size of 30 nm or less. Deodorizing material.
[0026] Section 11. An antibacterial and / or antiviral material, Contains zinc oxide nanoparticles and titania nanoparticles, The zinc oxide nanoparticles have an average particle size of 15 nm or less, The titania nanoparticles have an average particle size of 30 nm or less. Antibacterial and / or antiviral materials.
[0027] Section 12. An antiviral coating solution, The antibacterial and / or antiviral material according to item 11, and Contains water Antiviral coating liquid. Effect of the Invention
[0028] According to the present invention, in the method for producing zinc oxide nanoparticles, zinc oxide nanoparticles of 15 nm or less can be easily obtained by mixing zinc oxide and an organic acid in a specific ratio.
[0029] According to the present invention, zinc oxide having high transparency can be easily obtained.
[0030] According to the present invention, by mixing the zinc oxide nanoparticles with a composite of titania, the composite can be used as a highly safe, transparent, and highly active deodorizing, antibacterial, and antiviral material. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0031] In this specification, the term "containing" is a concept that encompasses all of "comprise," "consist essentially of," and "consist only of."
[0032] In this specification, when a numerical range is expressed as A to B, it indicates A or more and B or less.
[0033] In this specification, "titanium oxide" or "titania" does not only refer to titanium dioxide (TiO2), but also includes titanium trioxide (Ti2O3); titanium monoxide (TiO); and titanium dioxide having an oxygen deficiency, such as Ti4O7 and Ti5O9.
[0034] In this specification, "titanium oxide" or "titania" may contain groups other than Ti-O-Ti resulting from the synthesis of titanium oxide, such as terminal Ti-OH groups, TiCOCH3 groups, TiOCH2CH3 groups, TiOCH2CH2CH3 groups, TiOCH(CH3)CH3 groups, TiOCH2CH2CH2CH3 groups, TiOCOCH3 groups, etc.
[0035] In this specification, "titanium oxide" or "titania" also includes those having an organic acid or the like bonded to a terminal OH group.
[0036] 1. Manufacturing method of zinc oxide nanoparticles The method for producing zinc oxide nanoparticles of the present invention comprises the steps of: Zinc oxide (nanoparticles) and an organic acid are mixed in a mass ratio of The method includes a step of mixing zinc oxide (nanoparticles):organic acid=zinc oxide (nanoparticles) 1:organic acid 0.18 to 0.3.
[0037] The organic acid is mixed in a mass ratio of 0.18 to 0.3 for every 1 part of zinc oxide.
[0038] (1) Zinc oxide The zinc oxide nanoparticles of the present invention are prepared from zinc oxide particles having a larger average particle size than the target average particle size. The average particle size of the zinc oxide raw material is not particularly limited, but is preferably 20 nm to 300 nm, and more preferably 20 nm to 100 nm.
[0039] (2)Organic acid In the method for producing zinc oxide nanoparticles of the present invention, the organic acid is preferably acetic acid.
[0040] In this patent, an organic acid is mixed as a surface treatment agent for zinc oxide (nanoparticles).
[0041] Since organic acids are preferably volatile acids, they are represented by the chemical formula C n H 2n+1 Examples of the carboxylic acid include monocarboxylic acids represented by COOH (n=0 to 3) and hydroxycarboxylic acids having 2 to 3 carbon atoms.
[0042] Preferred monocarboxylic acids are formic acid (n=0) and acetic acid (n=1). Preferred hydroxycarboxylic acids are glycolic acid, lactic acid, etc., with acetic acid being particularly preferred from the standpoints of volatility, water solubility, safety, and odor.
[0043] These organic acids can be used alone or in combination of two or more.
[0044] When a volatile acid is used, the zinc oxide (nanoparticles) solution can be used directly for coating.
[0045] By using an appropriate amount of organic acid relative to zinc oxide (nanoparticles), zinc oxide with a small particle size can be obtained.
[0046] The mass ratio of zinc oxide (nanoparticles) to organic acid is preferably zinc oxide (nanoparticles) 1:organic acid 0.18 to 0.3, and more preferably zinc oxide (nanoparticles) 1:organic acid 0.19 to 0.25.
[0047] (3) Titania nanoparticles The zinc oxide nanoparticles of the present invention may be mixed with titania nanoparticles and used as a deodorizing, antibacterial and antiviral material.
[0048] The coexistence of titania nanoparticles enhances the deodorizing, antibacterial and antiviral properties.
[0049] The mixing ratio of zinc oxide (nanoparticles) and titania nanoparticles is not particularly limited, but is usually 1:100 zinc oxide (nanoparticles) to 1:0.01 titania, and from the viewpoint of synergistic effects of deodorizing, antibacterial, and antiviral properties, it is preferable that the mixing ratio is 1:10 titania to 1:0.1 zinc oxide (nanoparticles).
[0050] When titania nanoparticles are used together, those having a large specific surface area and high dispersibility in water are preferred.
[0051] The specific surface area of titania nanoparticles is 10m 2 / g~500m 2 / g is preferred, 45m 2 / g~400m 2 / g is more preferable, and 90m 2 / g~350m 2 / g is more preferred.
[0052] The diameter of the titania nanoparticles is preferably from 1 nm to 150 nm, more preferably from 1 nm to 30 nm, further preferably from 1 nm to 16 nm, and most preferably from 1 nm to 6 nm.
[0053] In particular, the titania nanoparticles of the present invention are preferably those that are uniformly dispersed in water, and can be produced, for example, by the following production method.
[0054] (A) a step of mixing a titanium-containing substance, an organic acid, and water to obtain a dispersion; (B) stirring the dispersion obtained in the step (A) for 5 minutes or more; and (C) heating the dispersion obtained in the step (B) at 70° C. or higher for 1 hour or more; and In the step (A), the mixture ratio of the titanium-containing substance and the organic acid is such that the amount of acyloxy groups in the organic acid is 0.4 mol or more per mol of titanium in the titanium-containing substance.
[0055] In the case of acetic acid, 2 moles or more is preferable, but in the case of lactic acid or citric acid, highly transparent titania nanoparticles can be obtained even with 0.5 moles or less.
[0056] <Process (A)> In step (A), a specific amount of a substance containing titanium, a specific amount of an organic acid, and water are mixed to obtain a dispersion.
[0057] The titanium-containing substance to be used is not particularly limited as long as it is a substance that becomes titanium oxide by heating. The titanium-containing substance is preferably titanium oxide and / or a titanium oxide precursor, and specifically includes titanium oxide; titanium hydroxide; titanium alkoxide; titanium halide such as titanium trichloride and titanium tetrachloride (particularly those neutralized with a base); metallic titanium, etc. Also, only one of these may be used, or two or more may be used in combination.
[0058] Among these, from the viewpoint of dispersibility of the obtained titania, titanium alkoxide, titanium hydroxide or titanium halide, particularly those neutralized with a base, are preferred, and titanium alkoxide is more preferred from the viewpoint of purity and dispersibility.
[0059] Examples of titanium alkoxides include titanium tetraisopropoxide, titanium tetra n-butoxide, titanium tetra n-propoxide, and titanium tetraethoxide. From the viewpoints of cost and water solubility of by-products, titanium tetraisopropoxide is preferred.
[0060] Depending on the combination of titanium alkoxide and organic acid, the resulting titania may act as a catalyst to liberate ester compounds that are poorly soluble in water. There is no problem with the titania itself. For example, when titanium tetra-n-butoxide and acetic acid are combined, butyl acetate is produced and liberated when they are mixed and heated.
[0061] From the viewpoint of obtaining a uniform dispersion, it is preferable to employ a combination of an organic acid and a titanium alkoxide that can provide an organic acid alkoxide having excellent water solubility.
[0062] Titanium halides (titanium tetrachloride, titanium trichloride, etc.) are preferably neutralized with a base and the precipitate washed from the viewpoints of impurities (halogens), corrosion of the reactor during mass production, and crystallinity control. In that case, it is preferable to use the titanium halides without drying from the viewpoint of dispersibility of the obtained titania.
[0063] When using a solid such as titanium oxide or metallic titanium, the average particle size is preferably 100 nm or less, more preferably 50 nm or less. The lower limit is not particularly set, but is usually about 1 nm. When the particle size is large, it may be ground in a dry or wet manner using a planetary ball mill, paint shaker, or the like. The average particle size can be measured, for example, by observation with an electron microscope (SEM or TEM).
[0064] The concentration of the titanium-containing substance in the dispersion is preferably 0.01 mol / L to 5 mol / L, and more preferably 0.05 mol / L to 3 mol / L, from the viewpoints of productivity and viscosity of the reaction liquid.
[0065] The acid used in the reaction is an organic acid, represented by the chemical formula C n H 2n+1 Monocarboxylic acids represented by COOH (n = 0-11), HOOCC m H 2m Examples thereof include dicarboxylic acids represented by COOH (m=0 to 8) and hydroxycarboxylic acids having 1 to 6 carbon atoms.
[0066] Of the monocarboxylic acids, acetic acid (n=1) is preferred from the viewpoints of solubility in water (especially those with n=4 or less are easily soluble in water) and odor (especially those with n=2 to 4 have a strong odor).
[0067] For the dicarboxylic acid, m is preferably 0 to 2 from the viewpoint of solubility in water, but m is more preferably 1 or 2 in consideration of dispersibility in titania.
[0068] Examples of hydroxycarboxylic acids include glycolic acid, lactic acid, malic acid, tartaric acid, and citric acid.
[0069] Of these, acetic acid and lactic acid are particularly preferred as the organic acid, from the viewpoint of being able to be removed later by volatilization.
[0070] These organic acids may be used alone or in combination of two or more.
[0071] From the viewpoints of dispersibility and cost, the amount of organic acid used is preferably adjusted so that the COOH group is contained in the titanium-containing substance in an amount of 0.4 mol or more, preferably 0.5 mol to 10 mol, per mol of titanium in the titanium-containing substance. The more organic acid is used, the more improved the dispersibility becomes.
[0072] The concentration of the organic acid in the dispersion is preferably from 0.005 mol / L to 10 mol / L, and more preferably from 0.02 mol / L to 7 mol / L, from the viewpoints of dispersibility and cost.
[0073] As the reaction solvent, it is preferable to use an aqueous solvent such as water as the main component (specifically, for example, 50% by weight or more), but alcohols or esters may be contained during the reaction.
[0074] For example, when titanium tetraisopropoxide is used as a raw material, it reacts with an organic acid to produce isopropanol, and may also produce isopropyl esters of organic acids upon heating.
[0075] Alcohols or esters may be added to the dispersion obtained in step (A) or may be generated in the system. The alcohols or esters may be removed by heating in an open system at 100° C. or less, or may remain in the reaction liquid.
[0076] When an alcohol is contained in the dispersion liquid, the particle size tends to become small, and therefore, in order to control the particle size, an alcohol may be intentionally added.
[0077] In the present invention, inorganic acids (especially strong inorganic acids) such as nitric acid, hydrochloric acid, and sulfuric acid, which are often used in hydrothermal synthesis reactions of titania nanoparticles, may be used. Carboxylic acids are preferred from the viewpoints of corrosion of equipment, impurities, wastewater, etc., in addition to the low adhesion of the resulting titania nanoparticles to the substrate.
[0078] Inorganic and organic acids can be used supplementarily to improve the dispersibility and uniformity of the raw material and to facilitate handling, without impairing the effect, for example, in the range of 0.01 mol / L or less. In this case, the concentrations of N, Cl, and S elements in the dispersion liquid are all 0.01 mol / L.
[0079] Of the inorganic acids and organic acids, nitric acid is preferred because it easily produces anatase-type titania, which has high transparency, and is easy to remove.
[0080] The pH of the dispersion obtained in step (A) is preferably 1.5 or more and less than 6, more preferably 2 to 5, from the viewpoints of corrosion of the apparatus, safety in handling, and dispersibility.
[0081] In step (A), the method for preparing the dispersion is not particularly limited, and the titanium-containing substance, the organic acid, and water (solvent) may be mixed simultaneously or successively. In particular, from the viewpoint of preventing aggregation and forming large lumps and enabling continuous stirring, it is preferable to mix the organic acid and water (solvent) and then add the titanium-containing substance while stirring.
[0082] On the other hand, if water is added dropwise to a mixture of a titanium-containing substance and an organic acid, the mixture is more likely to aggregate.
[0083] <Process (B)> In the step (B), the dispersion obtained in the step (A) is stirred for 5 minutes or more.
[0084] The stirring method is not particularly limited, and may be performed according to a conventional method. The stirring time is 5 minutes or more, preferably 15 minutes or more, from the viewpoint of sufficiently reacting the titanium-containing substance with the organic acid and water. The upper limit of the stirring time is not particularly limited, but is usually about 240 hours.
[0085] <Process (C)> In step (C), the dispersion obtained in step (B) is heated at 70° C. or higher for 1 hour or longer.
[0086] Step (C) may be carried out under normal pressure or under pressure in a closed vessel.
[0087] When heating is performed under pressure, it may be performed under supercritical conditions. More specifically, the pressure during heating is preferably 0.45 MPa or more, more preferably 1 MPa to 30 MPa, from the viewpoint of increasing the particle size. However, when a small particle size is acceptable, it is easier to perform the heating under normal pressure.
[0088] The heating temperature is 50° C. or higher, preferably 70° C. to 450° C., and more preferably 150° C. to 400° C. If the heating temperature is less than 50° C., highly active titania nanoparticles cannot be obtained.
[0089] When the reaction is carried out under normal pressure, the reaction temperature is preferably 50° C. to 120° C., and more preferably 70° C. to 110° C., from the viewpoint of obtaining titania nanoparticles having a smaller average particle size.
[0090] When the reaction is carried out under pressure (not supercritical), from the viewpoint of obtaining titania nanoparticles having a larger average particle size than those under normal pressure, the temperature is preferably 120° C. to 370° C., more preferably 150° C. to 300° C. In this case, the reaction may be first heated at a low temperature (e.g., 50° C. to 120° C.) and then heated to a high temperature (e.g., 120° C. to 370° C.).
[0091] When the reaction is carried out under supercritical conditions, even under pressure, the dispersion obtained in step (B) can be mixed with supercritical water in a flow reactor, for example, to synthesize titania nanoparticles with uniform particle size and a titania dispersion with extremely high dispersibility in an extremely short time. In this case, it is preferable to mix the dispersion obtained in step (B) at 50°C or less with supercritical water at 374°C or more and hold it at 300°C or more (particularly 375°C to 450°C) for 1 second or more (particularly 5 seconds to 600 seconds). When contacting with supercritical water, the reaction can be completed in an extremely short time.
[0092] The titania nanoparticles of the present invention thus obtained have significantly improved dispersibility compared to conventional titania nanoparticles.
[0093] In the composite of the present invention, the titania nanoparticles preferably have an average particle size of 30 nm or less.
[0094] The titania nanoparticles of the present invention have an average particle size of about 3 nm to 50 nm, and particularly about 4 nm to 40 nm.
[0095] By setting the average particle size of the titania nanoparticles within this range, the metal nanoparticles can be supported appropriately and more firmly, and a film having higher visible light catalytic activity and higher transparency can be formed.
[0096] Normally, when the average particle size is small, the shrinkage during heating is large, which makes it easy for cracks and peeling off from the substrate to occur. However, the metal nanoparticle-supported titania nanoparticles of the present invention are a material with excellent coatability, despite the use of titania nanoparticles with a small average particle size.
[0097] In the present invention, the average particle size of the titania nanoparticles is measured by observation with a transmission electron microscope (TEM).
[0098] The titania nanoparticles of the present invention have a specific surface area of 30 m 2 / g~500m 2 / g, especially 40m 2 / g~350m 2 / g is obtained.
[0099] By setting the specific surface area of the titania nanoparticles within this range, the metal nanoparticles can be supported appropriately and more firmly, and the visible light catalytic activity can be easily increased.
[0100] The specific surface area of the titania nanoparticles is measured by the BET method.
[0101] The titania nanoparticles of the present invention have N, Cl, and S element concentrations of 0 to 5,000 ppm, and particularly 0 to 1,000 ppm.
[0102] By setting the concentrations of N, Cl, and S elements in the titania nanoparticles within this range, it is easy to suppress corrosion of the substrate, etc. This condition means that there is no impurity derived from the acidic titania precursor such as TiCl4 or TiOSO4, or there is only a very small amount of it.
[0103] The concentrations of N, Cl, and S elements in the titania nanoparticles are measured by WDX (fluorescent X-ray).
[0104] The crystal form of the titania nanoparticles is preferably anatase type, which can particularly improve the visible light catalytic activity.
[0105] There are no other crystal forms than the anatase type, and it is preferable that the anatase type is 100%.
[0106] Thereafter, the titania nanoparticles of the present invention can be recovered by precipitating and centrifuging the titania nanoparticles of the present invention using a conventional method.
[0107] In this way, the titania nanoparticles of the present invention can be used to adjust the average particle size and specific surface area, and also have excellent dispersibility. Therefore, they can be used not only for photocatalysis (superhydrophilicity, decomposition of organic / inorganic substances, hydrogen production, etc.), but also for a wide variety of applications, such as dye-sensitized solar cells, transparent conductive films, catalyst supports, heat-resistant coatings, high refractive coatings, and heat-shielding coatings.
[0108] The titania dispersion used in the present invention can be made uniform by using the reaction liquid that has been subjected to the above steps (A) to (C) and adding a dispersion step such as ultrasonic dispersion.
[0109] In the composite of the present invention, preferably, the titania nanoparticles have acetoxy groups bonded to at least some of the titanium atoms present on the surface, and when the titania nanoparticles are heated to 600°C using a simultaneous differential thermal and thermogravimetric analyzer, the weight loss at 200°C or higher is 5% by mass or more.
[0110] In the present invention, the form of titania nanoparticles carrying metal nanoparticles (zinc oxide nanoparticles) is preferably adopted, and metal nanoparticle-carrying titania nanoparticles in which metal nanoparticles are carried on the surfaces of titania nanoparticles are preferred.
[0111] In the present invention, the titania nanoparticles preferably have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and metal nanoparticles are supported on the surface in an amount of 90 mass% or less relative to the titanium oxide in the titania nanoparticles.
[0112] In the present invention, preferably, when the temperature is raised to 600° C. using a thermogravimetric and differential thermal analyzer, the mass loss at 200° C. or higher is 5% by mass or more.
[0113] In the titania nanoparticles carrying metal nanoparticles (zinc oxide nanoparticles) of the present invention, the average particle size and specific surface area of both the titania nanoparticles and the metal nanoparticles can be adjusted, and the titania nanoparticles and the metal nanoparticles are firmly adhered to each other. In addition, the titania nanoparticles and the metal nanoparticles have excellent dispersibility and are not prone to aggregation, so that the coating property and transparency are excellent without the use of a separate additive such as a dispersant.
[0114] The metal nanoparticle (zinc oxide nanoparticle)-supported titania nanoparticles and photocatalyst of the present invention have sufficient coatability and transparency without the use of a separate dispersant, and therefore can have excellent visible light catalytic activity without the visible light catalytic activity being impaired by additives such as dispersants.
[0115] The metal nanoparticles (zinc oxide nanoparticles)-supporting titania nanoparticles of the present invention are useful as photocatalysts (particularly visible light-responsive photocatalysts).
[0116] Generally, water, inorganic acids, free organic acids, etc. volatilize almost entirely at temperatures below 200°C.
[0117] The titania nanoparticles constituting the metal nanoparticle (zinc oxide nanoparticle)-supporting titania nanoparticles of the present invention have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and therefore the acyloxy groups are gradually eliminated in the range of 200° C. to 600° C. For example, in the case of acetoxy groups, the acetoxy groups are gradually eliminated in the range of 200° C. to 600° C., with a peak at about 260° C.
[0118] The titania nanoparticles constituting the titania nanoparticles supporting metal nanoparticles (zinc oxide nanoparticles) of the present invention have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and therefore aggregation of the titania nanoparticles with each other during drying or firing can be suppressed, making them less susceptible to cracking, peeling, and the like. As a result, the titania nanoparticles are particularly excellent in coatability and transparency, and cracking, peeling, and the like can be suppressed. Furthermore, the metal nanoparticles described below can be easily supported firmly, resulting in excellent visible light catalytic activity.
[0119] It is generally known in the art that the presence of acyloxy groups on the surface generally reduces the visible light catalytic activity.
[0120] In the present invention, the aggregation of titania nanoparticles during drying or calcination can be suppressed, and therefore the effect of suppressing cracks, peeling, etc. is particularly excellent. In addition, since metal nanoparticles (zinc oxide nanoparticles) can be easily and firmly supported, visible light catalytic activity can also be improved despite the presence of acyloxy groups.
[0121] Titania nanoparticles preferably have a large number of acyloxy groups bonded to titanium atoms present on the surface. When acyloxy groups are present on at least some of the titanium atoms present on the surface, they are gradually released in the range of 200°C to 600°C, and therefore, when the temperature is increased using a thermogravimetric and differential thermal analyzer (TG-DTA), the mass loss is large at temperatures above 200°C.
[0122] In the present invention, when the temperature is increased using a thermogravimetry-differential thermal analyzer (TG-DTA), the mass loss at 200°C or higher represents an index of the number of acetoxy groups bonded to titanium atoms present on the surface.
[0123] When heated to 600° C. using a thermogravimetry and differential thermal analyzer (TG-DTA), the mass loss at 200° C. or higher is 5% by mass or more, preferably 7% by mass to 20% by mass. The detailed conditions for the thermogravimetry and differential thermal analyzer (TG-DTA) are as follows: atmosphere: air, heating rate: 3° C. / min.
[0124] Titania nanoparticles have acyloxy groups bonded to at least some of the titanium atoms present on the surface, and these acyloxy groups are preferably bonded to the titanium atoms via a group represented by -OCOR (wherein R represents a hydrogen atom, an alkyl group having 1 to 3 carbon atoms, or a hydroxyalkyl group having 1 to 2 carbon atoms).The acyloxy group is preferably an acyloxy group derived from an organic acid such as a monocarboxylic acid having 1 to 4 carbon atoms or a hydroxycarboxylic acid having 2 to 3 carbon atoms.
[0125] In the above R, preferred examples of the alkyl group include a methyl group, an ethyl group, and an n-propyl group.
[0126] In the above R, preferred examples of the hydroxyalkyl group include a hydroxymethyl group, a 1-hydroxyethyl group, and a 2-hydroxyethyl group.
[0127] Preferred examples of the monocarboxylic acid include formic acid, acetic acid, propionic acid, and butyric acid. Preferred examples of the hydroxycarboxylic acid include glycolic acid and lactic acid.
[0128] From the viewpoints of volatility, harmfulness and decomposability, R is preferably a hydrogen atom, or a methyl group, a hydroxymethyl group, a 1-hydroxyethyl group, a 2-hydroxyethyl group, or the like, and from the viewpoints of water solubility and odor, a methyl group is preferred.
[0129] From the viewpoints of volatility, harmfulness and decomposability, the monocarboxylic acid is preferably formic acid, acetic acid, etc., and the hydroxycarboxylic acid is preferably glycolic acid, lactic acid, etc.
[0130] Acetic acid is particularly preferred from the viewpoints of water solubility and odor.
[0131] The organic acids can be used alone or in combination of two or more kinds.
[0132] In conventional titania dispersions, a uniform dispersion could not be obtained unless a dispersing agent was used.
[0133] In the present invention, a dispersant may be added, but even without adding a dispersant, a dispersion liquid with much better dispersibility than normal titania nanoparticles can be obtained. As a result of the good dispersibility, the coating has excellent crack resistance. As a result of not adding a dispersant, a dense titania coating is possible.
[0134] In this case, in the titania dispersion of the present invention, the content of water as a solvent is preferably 60% by weight or more, particularly 75% by weight or more, from the viewpoints of ease of coating and film properties of the coating.
[0135] It is also possible to take out titania nanoparticles from the reaction solution and change the solvent. Water may be removed from the reaction solution by centrifugation or a filtration membrane, and the water may be replaced with an organic solvent. In this case, it is preferable not to dry the titania nanoparticles from the viewpoints of dispersibility, transparency, etc.
[0136] The organic solvent used in the dispersion liquid includes alcohols and the like.
[0137] Examples of the alcohols include aliphatic alcohols having 1 to 6 carbon atoms, such as methanol, ethanol, and isopropanol, as well as non-aliphatic alcohols, such as α-terpineol; glycol solvents, such as butyl carbitol (diethylene glycol monobutyl ether), hexylene glycol (2-methyl-2,4-pentanediol), ethylene glycol-2-ethylhexyl ether, ethylene glycol monomethyl ether, and propylene glycol monomethyl ether; and diols, such as 1,4-butanediol, 1,5-pentanediol, and 1,6-hexanediol.
[0138] The organic solvent used in the dispersion may not have an OH group, as long as it has affinity with titania and other solvents (water, alcohol, etc.), and examples of the organic solvent include diethylene glycol butyl methyl ether, tripropylene glycol dimethyl ether, triethylene glycol dimethyl ether, diethylene glycol dibutyl ether, triethylene glycol butyl methyl ether, tetraethylene glycol dimethyl ether, diethylene glycol monobutyl ether acetate, diethylene glycol monoethyl ether acetate, diethylene glycol diacetate, triethylene glycol diacetate, tetraethylene glycol diacetate, etc. Among these, diethylene glycol monobutyl ether acetate, tetraethylene glycol dimethyl ether, etc. are preferred from the viewpoint of boiling point, etc.
[0139] 2. Zinc oxide nanoparticles The zinc oxide nanoparticles of the present invention are The zinc oxide nanoparticles have an acyloxy group bonded to at least a part of the zinc oxide present on the surface, Specific surface area is 70m 2 / g or more.
[0140] In the zinc oxide nanoparticles of the present invention, preferably, when the zinc oxide nanoparticles are heated up to 600° C. using a thermogravimetric and differential thermal analyzer, the weight loss at 200° C. or higher is 3% by mass or more.
[0141] In the zinc oxide nanoparticles of the present invention, the average particle size of the zinc oxide nanoparticles is preferably 15 nm or less.
[0142] 3. Photocatalysts, composites, antibacterial and / or antiviral materials, and antiviral coating solutions The photocatalyst of the present invention contains the zinc oxide nanoparticles.
[0143] The composite of the present invention contains the zinc oxide nanoparticles and titania nanoparticles.
[0144] The deodorant material of the present invention contains zinc oxide nanoparticles and titania nanoparticles, The zinc oxide nanoparticles have an average particle size of 15 nm or less, The titania nanoparticles have an average particle size of 30 nm or less.
[0145] The antibacterial and / or antiviral material of the present invention contains zinc oxide nanoparticles and titania nanoparticles, The zinc oxide nanoparticles have an average particle size of 15 nm or less, The titania nanoparticles have an average particle size of 30 nm or less.
[0146] The antiviral coating liquid of the present invention contains the antibacterial and / or antiviral material and water.
[0147] The viscosity of the antiviral coating liquid of the present invention is adjusted depending on the application. For example, when it is used for spin coating, dip coating, spraying, or the like, it is adjusted to a low viscosity.
[0148] When the antiviral coating liquid of the present invention is used for brush application, squeegee method, or the like, the viscosity is adjusted to be higher.
[0149] When the antiviral coating liquid of the present invention is used for screen printing, it is preferable to adjust the viscosity to be higher and suppress the fluidity.
[0150] The coating of the present invention is a dense coating. EXAMPLES
[0151] The present invention will now be described in detail with reference to examples.
[0152] The present invention is not limited to these.
[0153] [Example 1] 85.6 g of water was added to 10 g of 20 nm zinc oxide and stirred. Then, 2.0 g of acetic acid was added and stirred for another 30 minutes (zinc oxide and organic acid were mixed in a mass ratio of zinc oxide 1:organic acid 0.2).
[0154] This liquid was spin-coated at 2,000 rpm for 60 seconds, resulting in a transparent coating with good adhesion.
[0155] This liquid was diluted 10 times and applied to the inside of a 20 ml glass bottle. After the excess liquid was removed, it was dried to form a transparent coating.
[0156] Methylene blue was added to the glass bottle, and the output was 2,000 mW / cm 2 When exposed to ultraviolet light, it became completely colorless within 30 minutes.
[0157] In comparison with Comparative Example 5, the photocatalytic effect was higher than that of titania having a high specific surface area.
[0158] The liquid was filtered under reduced pressure and dried in vacuum at 200°C.
[0159] The BET specific surface area was measured and found to be 91m 2 / g and the estimated particle size was 11.8 nm.
[0160] [Example 2] 85.6 g of water was added to 10 g of 20 nm zinc oxide and stirred. Then, 2.0 g of acetic acid was added and stirred for 5 minutes (zinc oxide and organic acid were mixed in a mass ratio of zinc oxide 1:organic acid 0.2).
[0161] 120 g (2 mol) of acetic acid was added to 142.1 g (0.5 mol) of titanium tetraisopropoxide and stirred for 15 minutes, and then 550 g of water was added. The pH of this dispersion was 2.5.
[0162] A large amount of translucent precipitate was generated, but after stirring for 60 minutes and heating at 60°C, the precipitate was completely dissolved.
[0163] After that, the mixture was stirred at normal pressure (0.1 MPa) at 80°C for 5 hours, and then water was added to the reaction liquid to make a total of 800 g. After that, ultrasonic waves were applied to the mixture, and a translucent, uniform titania dispersion was obtained without using a strong inorganic acid.
[0164] 5 g of this zinc oxide dispersion, 10 g of the titania dispersion, and 5 g of water were mixed together to prepare a coating liquid.
[0165] This liquid was coated onto silicon and an antibacterial test was conducted, and 99.5% of E. coli was killed within one hour.
[0166] [Example 3] 85.6 g of water was added to 10 g of 20 nm zinc oxide and stirred. Then, 2.0 g of acetic acid was added and stirred for 5 minutes (zinc oxide and organic acid were mixed in a mass ratio of zinc oxide 1:organic acid 0.2).
[0167] 120 g (2 mol) of acetic acid was added to 142.1 g (0.5 mol) of titanium tetraisopropoxide and stirred for 15 minutes, and then 550 g of water was added. The pH of this dispersion was 2.5.
[0168] A large amount of translucent precipitate was generated, but after stirring for 60 minutes and heating at 60°C, the precipitate was completely dissolved.
[0169] After that, the mixture was stirred at normal pressure (0.1 MPa) at 80°C for 5 hours, and then water was added to the reaction liquid to make a total of 800 g. After that, ultrasonic waves were applied to the mixture, and a translucent, uniform titania dispersion was obtained without using a strong inorganic acid.
[0170] 10 g of this dispersion containing 5 wt % titania, 10 g of water, and 0.039 g of silver acetate were added and stirred, and 0.5 g of the zinc oxide dispersion was further added (titania:zinc oxide=10:1) and ultrasonic dispersion was performed, resulting in a white, uniform dispersion.
[0171] The resulting solution was spin-coated three times on a 50 mm square glass substrate at 1,000 rpm for 60 seconds to obtain a transparent coating film.
[0172] The antiviral properties of this test specimen were evaluated using feline coronavirus in accordance with JIS R 1756 (conditions: visible light illuminance 1,000 Lx x 8 hours). As a result, the antiviral activity value was 2.0 (99% inactivation), confirming high antiviral properties.
[0173] In addition, when the antiviral properties were evaluated in a dark place, the antiviral activity value was 5.0 or higher (99.999% or more inactivated), confirming high antiviral properties.
[0174] [Comparative Example 1] 89 g of water was added to 10 g of 20 nm zinc oxide and stirred. Then, 1.0 g of acetic acid was added and stirred for another 30 minutes.
[0175] The liquid was filtered under reduced pressure and dried in a vacuum at 200°C. The BET specific surface area was measured and found to be 30.4 m 2 / g and the estimated particle size was 35.2 nm, which was larger than the particle size of the original zinc oxide.
[0176] [Comparative Example 2] 88.75 g of water was added to 10 g of 20 nm zinc oxide and stirred. Then, 1.25 g of acetic acid was added and stirred for another 30 minutes.
[0177] The liquid was filtered under reduced pressure and dried in a vacuum at 200°C. The BET specific surface area was measured and found to be 29.4 m 2 / g and the estimated particle size was 36.4 nm.
[0178] [Comparative Example 3] 88.5g of water was added to 10g of 20nm zinc oxide and stirred. Then, 1.5g of acetic acid was added and stirred for another 30 minutes.
[0179] The liquid was filtered under reduced pressure and dried in a vacuum at 200°C. The BET specific surface area was measured and found to be 30.1 m 2 / g and the estimated particle size was 35.6 nm.
[0180] [Comparative Example 4] 88.5 g of water was added to 10 g of 20 nm zinc oxide and stirred. Then, 1.75 g of acetic acid was added and stirred for another 30 minutes.
[0181] The liquid was filtered under reduced pressure and dried in a vacuum at 200°C. The BET specific surface area was measured and found to be 38.4 m 2 / g and the estimated particle size was 27.9 nm.
[0182] [Comparative Example 5] The test was carried out in the same manner as in Example 3, except that no zinc oxide dispersion was added.
[0183] When only the titania dispersion liquid was coated onto silicon and an antibacterial test was carried out, 51.5% of the Escherichia coli was killed within one hour, but this was inferior to Example 2.
[0184] [Comparative Example 6] 120 g (2 mol) of acetic acid was added to 142.1 g (0.5 mol) of titanium tetraisopropoxide and stirred for 15 minutes, and then 550 g of water was added. The pH of this dispersion was 2.5.
[0185] A large amount of translucent precipitate was generated, but after stirring for 60 minutes and heating at 60°C, the precipitate was completely dissolved.
[0186] After that, the mixture was stirred at normal pressure (0.1 MPa) at 80°C for 5 hours, and then water was added to the reaction liquid to make a total of 800 g. After that, ultrasonic waves were applied to the mixture, and a translucent, uniform titania dispersion was obtained without using a strong inorganic acid.
[0187] Using this solution, a test was carried out in the same manner as in Example 1. The solution was diluted 5 times to make the titania concentration 1 wt%, and the solution was applied to the inside of a 20 ml glass bottle. After removing excess solution, the solution was dried to form a transparent coating film.
[0188] Methylene blue was added to the glass bottle, and the output was 2,000 mW / cm 2 When irradiated with ultraviolet light at 400 nm, the color became completely colorless in 50 minutes, which took longer than in Example 1.
[0189] Using this solution, a test was carried out in the same manner as in Example 3.
[0190] When only the titania dispersion liquid was coated onto silicon and an antibacterial test was carried out, 51.5% of the Escherichia coli was killed within one hour, but this was inferior to Example 2.
Claims
1. 1. A method for producing zinc oxide nanoparticles, comprising the steps of: Zinc oxide and an organic acid are mixed in a mass ratio of The process includes mixing zinc oxide and organic acid in a ratio of 1:0.18 to 0.3; The organic acid is at least one organic acid selected from the group consisting of monocarboxylic acids represented by the chemical formula C n H 2n+1 COOH (n=0 to 3) and hydroxycarboxylic acids having 2 to 3 carbon atoms.
2. The method according to claim 1, wherein the organic acid is acetic acid.
3. The zinc oxide nanoparticles have an acyloxy group bonded to at least a portion of the zinc oxide present on the surface, Specific surface area is 70m 2 The method according to claim 1 or 2, wherein the molecular weight of the polymer is 1000 or more.
4. 4. The method according to claim 3, wherein the zinc oxide nanoparticles undergo a weight loss of 3% by mass or more at 200°C or higher when heated to 600°C using a thermogravimetry and differential thermal analyzer.
5. The method according to claim 3 or 4, wherein the zinc oxide nanoparticles have an average particle size of 15 nm or less.
6. The method according to any one of claims 1 to 5, which is a method for producing a photocatalyst.
7. A method for producing a composite, comprising the steps of: A method for producing a zinc oxide nanoparticle, which further comprises mixing the zinc oxide nanoparticle produced by the method for producing a zinc oxide nanoparticle according to any one of claims 1 to 5 with titania nanoparticles.
8. 8. The method according to claim 7, wherein the titania nanoparticles have an average particle size of 30 nm or less.
9. The titania nanoparticles have acetoxy groups bonded to at least some of the titanium atoms present on the surface, 9. The method according to claim 7, wherein the titania nanoparticles undergo a weight loss of 5% by mass or more at 200° C. or higher when heated to 600° C. using a thermogravimetric and differential thermal analyzer.
10. The zinc oxide nanoparticles have an average particle size of 15 nm or less, The titania nanoparticles have an average particle size of 30 nm or less, The method according to any one of claims 7 to 9, which is a method for producing a deodorizing material.
11. The zinc oxide nanoparticles have an average particle size of 15 nm or less, The titania nanoparticles have an average particle size of 30 nm or less. The method according to any one of claims 7 to 9, which is a method for producing an antibacterial or antiviral material.
12. The method for producing an antiviral coating liquid according to claim 11, further comprising adding water to the antiviral material.
Citation Information
Patent Citations
Zinc oxide particles with controlled color properties, method for producing same, and coating composition that includes said zinc oxide particles
WO2017134910A1